Pengaruh Koneksi Politik dan Transaksi Pihak Berelasi terhadap Manajemen Laba pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Hendi Hendi; Ika Putri Wahyu Ningsih (Faculty of Economics, Universitas Internasional Batam, 2019)
The purpose of this research is to find out the influence of political connections and transactions on related parties to earnings management in companies that have been listed on the Indonesia Stock Exchange. The theory states that managers can engage in self-enriching transactions at the detriment of the shareholders of the firm as to do an earnings management. In addition, politically connected companies are also suspected of using their connections to do an earnings management. In this study, the data used were obtained through the Indonesia Stock Exchange website starting in 2013 till 2017 with a population of 71 companies that had met the criteria and were selected using the purposive sampling method until the final total data sample used was 329 observational data. This study identifies the political connection variable does not have a significant effect on earnings management, however the abnormal liability related party transaction variable has a significant negative and abnormal sales of related party transaction variable has a significant positive effect on earnings management.